Comparative Studies Of The Biology, Life Tables And Water Balance Of The Turkestan Cockroach Blatta lateralis (Walker), German Cockroach Blattella germanica (L.) And Brown-Banded Cockroach Supella longipalpa (Fabricius) (Dictyoptera: Blattidae, Blattellidae) - Low, Kathleen Su Yin (2018)
The selected biological parameters such as adult longevity, fecundity and nymphal development of the Turkestan cockroach, Blatta lateralis (Walker) under laboratory controlled environment in comparison with the brown-banded cockroach, Supella longipalpa (Fabricius) and the German cockroach, Blattella germanica (L.) were studied. Results obtained demonstrated that the adult longevity of B. lateralis was the highest among the three cockroach species while the male to female ratio skewed towards the male with a ratio of 1.12:1.00. Among the three species, the adult females of B. lateralis were able to produce a significantly high number of oothecae (with a maximum number recorded at 39 oothecae) over their life span.